Estimation of the dimensional variability in the properties of soils in the basement of the atomic power station (APS) territory - A. S. Gousseltsev; V. V. Pendin; G. P. Barulin; D. N. Gorobtsov (Известия высших учебных заведений: Геология и разведка)
A method of the estimating the variability of the physical and mechanical characteristics of soils has been considered. The applying of this method in practice can be used to find out the weakened zones and tectonic structures at the territory of the atomic power stations, and also - traditionally - to estimate the influence on the behavior of the elementary natural technical system «construction - soils». The tasks of the revealing the character of the occurrence of the various possible structural non-homogeneities, which may influence on the atomic power station territory estimation, as well as a general plan allocation, have been estimated in geological parameters fields’ assessment at the one of the constructed atomic power stations territory and environs. The characteristics of the physical properties (humidity, density, zero-air dry unit weight, index fluidity) have been compared on the base of the analyses of the laboratory tests. The analysis has been done for a layer-marker which corresponds to the chalk deposits of the Turonian stage. A selective analysis of the dimensional variability of the soils’ properties has been done for the engineering-geological researches results on the territory of the atomic power-station and, in particular, reactor divisions. It has been concluded, that to make a right forecast, the additional engineering and geological investigations of the atomic power station are needed. Such researches will allow the sustainable definition, or confirmation, of the existing deformation and strength properties of the soils which are in the basement of the buildfngs for the depth, which is deeper than compressible thickness depth.